The structure of the serotonin system: A PET imaging study - Beliveau, Vincent; Ozenne, Brice; Strother, Stephen; Greve, Douglas N.; Svarer, Claus; Knudsen, Gitte Moos; Ganz, Melanie (NeuroImage (Orlando, Fla.), 2020)
The human brain atlas of the serotonin (5-HT) system does not conform with commonly used parcellations of neocortex, since the spatial distribution of homogeneous 5-HT receptors and transporter is not aligned with such brain regions. This discrepancy indicates that a neocortical parcellation specific to the 5-HT system is needed. We first outline issues with an existing parcellation of the 5-HT system, and present an alternative parcellation derived from brain MR- and high-resolution PET images of five different 5-HT targets from 210 healthy controls. We then explore how well this new 5-HT parcellation can explain mRNA levels of all 5-HT genes. The parcellation derived here represents a characterization of the 5-HT system which is more stable and explains the underlying 5-HT molecular imaging data better than other atlases, and may hence be more sensitive to capture region-specific changes modulated by 5-HT. •We evaluate a previous parcellation of the 5-HT system and propose an improvement.•Our new parcellation achieves a higher explained variance and is more stable.•The parcellation includes less regions, so region-based analysis are less penalized.•mRNA data for the HTR1A, HTR1F and HTR2C genes are well captured by the parcellation.